2004
DOI: 10.1592/phco.24.17.1784.52334
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Myotoxicity: Case Reports and Literature Review

Abstract: Two of our patients experienced myotoxicity associated with colchicine administration. The first was a 54-year-old woman who was receiving dialysis and came to the emergency department with progressive generalized weakness and vomiting. She recently had taken colchicine for the treatment of gout. Physical examination revealed proximal muscle weakness and tenderness on palpation. Her creatine kinase (CK), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels were elevated at 7185, 563, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 56 publications
6
89
1
8
Order By: Relevance
“…The bulk of the relevant mechanisms proposed so far to explain colchicineinduced muscle toxicity hinge on the disruption of the microtubule network. 2,3 In this study, we report data which support an expansion of the paradigm regarding the mechanism of colchicineinduced muscle toxicity from mere disruption of the microtubule network to a functional and/or synergistic relationship between colchicine and autophagy induction. We have shown that mice treated for 10 d with both colchicine and autophagic inducers such as rapamycin or simvastatin display (1) increased accumulation of autophagic substrates and ubiquitinated proteins; and (2) worsening of the colchicine-induced muscle pathology when compared with mice injected with colchicine alone.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The bulk of the relevant mechanisms proposed so far to explain colchicineinduced muscle toxicity hinge on the disruption of the microtubule network. 2,3 In this study, we report data which support an expansion of the paradigm regarding the mechanism of colchicineinduced muscle toxicity from mere disruption of the microtubule network to a functional and/or synergistic relationship between colchicine and autophagy induction. We have shown that mice treated for 10 d with both colchicine and autophagic inducers such as rapamycin or simvastatin display (1) increased accumulation of autophagic substrates and ubiquitinated proteins; and (2) worsening of the colchicine-induced muscle pathology when compared with mice injected with colchicine alone.…”
Section: Discussionsupporting
confidence: 57%
“…One example of a toxic myopathy is colchicine-induced myopathy. 2 Colchicine is commonly used for the treatment of gouty arthritis, often at high initial doses. Colchicine myopathy is characterized by myalgias, muscle weakness, and occasional rhabdomyolysis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations